Effects of dibutyl phthalate on early implantation events with human endometrial cells and trophoblast spheroid model - Wonmo Lee; Inyoung Kang; Jin Hyun Jun; Jaewang Lee (Clinical and Experimental Reproductive Medicine, 2026)
Objective: This study investigates the estrogenic activity of dibutyl phthalate (DBP) and its potential effects on endometrial receptivity and early embryo implantation. Given its widespread exposure and structural similarities to endocrine-disrupting chemicals, the potential for DBP to interfere with implantation—a key factor in fertility—is explored.Methods: The optimal concentration of DBP was determined using the Cell Counting Kit-8 assay. Gene and protein expression related to attachment, estrogen receptor signaling, and inflammation were analyzed by reverse transcription quantitative polymerase chain reaction and western blotting. Immunocytochemistry was used to assess the nuclear translocation of estrogen receptor alpha (ERα), while attachment and outgrowth assays evaluated the effects of DBP on trophoblast behavior. Statistical analyses were performed using GraphPad Prism 5.01 (GraphPad Software) and SPSS ver. 18.0 (SPSS Inc.).Results: DBP did not show cytotoxicity in Ishikawa cells at concentrations of 1, 10, and 100 μM. DBP treatment upregulated the expression of genes related to attachment, estrogen receptor signaling, and inflammation. Protein analysis showed an increase in inflammation-related proteins, and DBP enhanced ERα nuclear translocation. In trophoblast experiments, DBP-treated cells exhibited slightly lower attachment rates at early time points, but no significant differences were observed after 1 hour. DBP also reduced the outgrowth area of JEG-3 cells, with a significant decrease observed at 100 μM.Conclusion: DBP exhibits estrogenic activity, disrupting implantation and invasion, and may pose risks to female reproductive health. These findings highlight the need for further investigation into the long-term effects of DBP exposure.